Peningkatan Hasil Belajar Peserta Didik Melalui Penerapan Metode Kerja Kelompok Pada Mata Pelajaran Bahasa Indonesia - Diana Ratna Sari; Sudrajat Sudrajat; Sati Sati (CV. ULIL ALBAB CORP, 2024)
This research aims to describe the use of group work methods in learning Indonesian to improve student learning outcomes. The subjects of this research were grade 1 students of Bina Insan Mulia Elementary School, Cisaat Village, Dukupuntang District, Cirebon Regency. The research method used is the Group Work method with the STAD type (Students Teams Achievement Divisions) in the form of classroom action research (PTK). The design in this research is the Kemmis and Taggart model. Kemmis and Taggart's model consists of four steps, namely planning, implementation, observation and reflection. The results of research in cycle I and cycle II showed an increase in student learning outcomes. This is evident from the data obtained from the research, there was an increase in the pre-cycle, there were 4 students (23.52%) who completed or met the group learning indicators. Therefore, action was taken in cycles I and II. In cycle I, the ability of students learning in groups increased to 8 students (47.05%). Then continued in cycle II and there was an increase in learning abilities in groups as many as 12 students (70.58%) reached the complete criteria or met the critical thinking ability indicators and 5 students (29.42%) had not yet reached the complete criteria.